EXPERIMENTAL STUDY ON DAMAGE IDENTIFICATION OF RECYCLED CONCRETE BEAM BY NEUTRAL AXIS POSITION - WANG XueHang; YANG QiuWei; ZHAO JingYun; ZHANG Ying; LU Chen; LIANG ChaoFeng; SUN BinXiang (Jixie qiangdu)
The intersection of neutral layer and the transverse section is called neutral axis. The position of neutral-axis will be changed when the corresponding beam structure is damaged. In this work, the static loading test of recycled concrete beam is carried out to verify the damage detection method based on neutral axis position. Experimental results show that structural damage can be detected by the change of the neutral-axis position.